2011
DOI: 10.1007/s00299-011-1022-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of major allergens Ara h 1, 2, 3 in peanut seed

Abstract: Peanut is among the most commonly used dietary seeds, but peanut allergens, especially Ara h 1 (Arachis hypogaea allergy 1), 2 and 3, can cause severe IgE-mediated reactions. In this study, the molecular characterization and expression pattern of three allergens in peanut LUHUA 8, the representative of the cultivated lines in China, are reported. In situ hybridization and real time PCR analysis revealed high expression levels and different tissue expression patterns of the three allergens, which might be conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Notably, SSCG1-12 was extremely highly expressed in the seeds, and specifically, SSCG1 and SSCG6 were abundantly expressed during all five seed development stages (Fig 2). Functional prediction analysis revealed that these SSCGs encoded nutrient reservoir proteins or allergen proteins (Table 1), whose transcripts are considered widely expressed specifically in mature peanut seed [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, SSCG1-12 was extremely highly expressed in the seeds, and specifically, SSCG1 and SSCG6 were abundantly expressed during all five seed development stages (Fig 2). Functional prediction analysis revealed that these SSCGs encoded nutrient reservoir proteins or allergen proteins (Table 1), whose transcripts are considered widely expressed specifically in mature peanut seed [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Food allergy is an increasing problem and legume seed proteins frequently cause allergic responses. ,, As a first step in determining whether glycosylation of legume proteins has a role in food allergy the N-glycome of the Lotus seed globulins including the abundant LCP2, the homologue of peanut Ara h 1, was determined. The N-glycans were released in-solution using PNGase A followed by characterization and relative quantification using PGC-LC–MS/MS.…”
Section: Resultsmentioning
confidence: 99%
“…All of these are insoluble in water but soluble in high-salt solvents. Several seed globulins are known to be allergens. , The general assumption is that legume food allergy is caused by aberrant proteolytic digestion in the gastrointestinal tract where proteolytic enzymes are located. Partially degraded peptides of more than six to eight amino acid residues can cross into the blood circulation with their epitopes exposed on MCH II receptors on antigen-presenting B-cells. Following initial exposure to such an allergen, specific IgE antibodies will be produced that maintain a background level over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation